2019
DOI: 10.1002/adem.201901015
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Oxygen‐Free Copper Processed by High‐Pressure Torsion after Room Temperature Storage for 12 Months

Abstract: Ultrafine‐grained copper samples produced by high‐pressure torsion are stored at room temperature for 12 months to investigate microstructural stability and the self‐annealing phenomena. The results show that samples processed by low numbers of turns exhibit less thermal stability after storage for 12 months in comparison with samples processed by high numbers of turns. A significant decrease in the hardness is recorded near the edges of the discs processed by 1/4, 1/2, and 1 turn due to recrystallization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
(115 reference statements)
1
4
0
Order By: Relevance
“…Higher strain amplitudes and accumulated strains also favor dislocation annihilation within the UFG structures generated during SPD. As a result, the microstructure of Cu specimens deformed under higher Δ ε will exhibit an extended free path for the moving dislocations unlocked due to changes in the strain path . This is consistent with the TEM observations in copper after MDF processing up to ε = 10.8 which revealed the existence of a denser dislocation network inside boundaries created during deformation at lower strain amplitudes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Higher strain amplitudes and accumulated strains also favor dislocation annihilation within the UFG structures generated during SPD. As a result, the microstructure of Cu specimens deformed under higher Δ ε will exhibit an extended free path for the moving dislocations unlocked due to changes in the strain path . This is consistent with the TEM observations in copper after MDF processing up to ε = 10.8 which revealed the existence of a denser dislocation network inside boundaries created during deformation at lower strain amplitudes.…”
Section: Discussionsupporting
confidence: 86%
“…The 0.2% yield strength for a given MDF cycle was determined based on the SS curve of the first compression step in the following cycle in which the loading direction is orthogonal to the previous compression direction. A line was drawn in Figure a using an equation from a recent study fitted based on data for SPD‐processed copper …”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the present data gives average hardness values across each disk of ≈594 ± 18 Hv after five turns but a slightly lower value at ≈584 ± 17 Hv after ten turns. Several investigations examined the effect of a temperature rise during HPT processing, but it was concluded that the increase in temperature is of relatively minor significance in initiating dynamic recrystallization . Accordingly, the hardness drop and the corresponding limited grain coarsening in the 5–10 turns of the HPT‐processed Mo samples are not attributed to a temperature rise but rather they are consistent with the occurrence of minor dynamic recovery at these high strain levels.…”
Section: Resultsmentioning
confidence: 97%
“…[37][38][39] Recent investigations examined the temperature rise and corresponding microstructure changes in Al, Ag, and Cu during HPT processing and it was concluded that the temperature rise is of only minor significance in initiating dynamic recrystallization. [40,41] Accordingly, the recrystallization phenomenon in Al-0.1% Mg alloy appears to be mainly due to the formation of large fractions of lattice defects from the heavy shear strains.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports investigated the temperature rise due to heat generated during plastic deformation and friction inherent in the material flow during the anvil rotation through finite element modeling . Recent investigations examined the temperature rise and corresponding microstructure changes in Al, Ag, and Cu during HPT processing and it was concluded that the temperature rise is of only minor significance in initiating dynamic recrystallization . Accordingly, the recrystallization phenomenon in Al–0.1% Mg alloy appears to be mainly due to the formation of large fractions of lattice defects from the heavy shear strains.…”
Section: Discussionmentioning
confidence: 99%